Clinical and biochemical discriminants between functional hypothalamic amenorrhoea (FHA) and polycystic ovary syndrome (PCOS). (19th January 2021) - Phylactou, Maria; Clarke, Sophie A.; Patel, Bijal; Baggaley, Caitlin; Jayasena, Channa N.; Kelsey, Tom W.; Comninos, Alexander N.; Dhillo, Waljit S.; Abbara, Ali
Abstract: Background: Secondary oligo/amenorrhoea occurs in 3%–5% of women of reproductive age. The two most common causes are polycystic ovary syndrome (PCOS) (2%–13%) and functional hypothalamic amenorrhoea (FHA) (1%–2%). Whilst both conditions have distinct pathophysiology and their diagnosis is supported by guidelines, in practice, differentiating these two common causes of menstrual disturbance is challenging. Moreover, both diagnoses are qualified by the need to first exclude other causes of menstrual disturbance. Aim: To review clinical, biochemical and radiological parameters that could aid the clinician in distinguishing PCOS and FHA as a cause of menstrual disturbance. Results: FHA is uncommon in women with BMI > 24 kg/m 2, whereas both PCOS and FHA can occur in women with lower BMIs. AMH levels are markedly elevated in PCOS; however, milder increases may also be observed in FHA. Likewise, polycystic ovarian morphology (PCOM) is more frequently observed in FHA than in healthy women. Features that are differentially altered between PCOS and FHA include LH, androgen, insulin, AMH and SHBG levels, endometrial thickness and cortisol response to CRH. Other promising diagnostic tests with the potential to distinguish these two conditions pending further study include assessment of 5‐alpha‐reductase activity, leptin, INSL3, kisspeptin and inhibin B levels. Conclusion: Further data directly comparing the discriminatory potential of these markers to differentiate PCOS and FHA in women with secondary amenorrhoea would be of value in defining an objective probability for PCOS or FHA diagnosis.